Pembelajaran Cooperative Learning Make A Match dalam Meningkatkan Minat Belajar Siswa - Marlina, Marlina (JURNAL AL-QAYYIMAH, 2019)
This article examines about learning Cooperative learning Make A Match in increasing student learning interest. This paper uses a qualitative descriptive method with the type of library research. The results showed that the Make a match method is one of the types of cooperative learning methods. One of the advantages of this technique is that students find a partner while learning about a concept or topic in a fun atmosphere. Interest and learning is an integral part because the intensity of one will implicates the outcome of the other. One who has a high interest in learning has the opportunity to obtain high learning outcomes and so is the opposite.